Soil Phytomining: Recent Developments—A Review - Christos Kikis; Georgios Thalassinos; Vasileios Antoniadis (Soil Systems, 2024)
Phytomining (PM) is defined as the process of using plants capable of bio-extracting metals from soil in order to explore them economically. This relatively new, innovative method has been gathering significant attention in both the academic and commercial domains. Conventional mining methods are often economically unviable when applied to lean ores, and they can lead to secondary pollution in soil—a situation that applies to all excavated metals. On the other hand, PM is an environmentally friendly and economically viable solution that addresses the growing demands for metal resources, while simultaneously contributing to energy production by harnessing biomass energy. This comprehensive review presents the current PM techniques, challenges, and the hyperaccumulator plant species that may be used for the extraction of the main targeted elements in the process. Typically, the targeted metals are those of economic value, which can later be deposited or sold to various industries. This review also analyzes the factors influencing the economic viability of PM and proposes potential enhancements. Undeniably, PM offers the opportunity for economically sustainable exploration of metal-rich soils, but its full commercial viability remains constrained under current conditions as scientists are actively searching for the identification and utilization of new hyperaccumulator plant species in different locations worldwide, while creating new relationships and business avenues within the mining industry. Overall, this review highlights the current status of PM technology and the plants used, emphasizing the need for further research to enhance its commercial implementation and its potential to assist the mining industry. We conclude that PM, although a relatively new and unexplored concept, may provide economic and environmental benefits to soil end-users and managers who must cultivate on metal-contaminated soils as PM may turn yield shortages (of specific commercial crops) to benefits if high-yield hyperaccumulators are cultivated for industrial valorization of their high metal-content biomass.